Pengaruh Kecerdasan Spiritual, Gaya Kepemimpinan Transformasional, dan Kecerdasan Emosional Terhadap Efisiensi Perangkat Pemerintahan Desa di Desa Nagerawe dan Focolodo Rawe Kabupaten Nagekeo - Sarlianus Poma (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2024)
The aim of this research is to ascertain the impact of three different variables on the performance of village government officials in the villages of Nagerawe and Focolodo Rawe, Nagekeo Regency: spiritual intelligence, emotional intelligence, and transformational leadership style. This study used a quantitative approach. In this study, 54 respondents served as samples. Purposive sampling was the method of sampling that was employed in this investigation. This study's findings established that (1) the Spiritual Intelligence Variable (X1) had a Value of Significance of 0.027 ? 0.05 and a Value of tcount of 2.839 ? the Value of ttable 2.008, indicating a significant influence of the Spiritual Intelligence Variable (X1) on the Performance Variable (Y). The results indicate that there was no significant effect of the Transformational Leadership Style Variable (X2) on the Performance Variable (Y). The value of tcount was 1.513 ? the value of ttable 2.008, and the value of significance was 0.137 > 0.05. (3) The Emotional Intelligence Variable (X3) was shown to have a substantial impact on the Performance Variable (Y) with a value of significance of 0.035 < 0.05 and a value of tcount of 2.203 ? the value of ttable 2.008. According to the simultaneous F-test results, the spiritual intelligence variable (X1), the transformational leadership style variable (X2), and the emotional intelligence variable (X3) all had an impact on the performance variable (Y) at the same time. The significance value was 0.000 ? 0.05 and the Fcount value was 30.292 ? the value of Ftable 2.790. The adjusted R square, or coefficient of determination, was found to be 0.624 by the coefficient of determination (R2) test. This indicates that the Spiritual Intelligence Variable (X1), Transformational Leadership Style Variable (X2), and Emotional Intelligence Variable (X3) accounted for 62.4% of the study's Performance Variable (Y), with other variables accounting for the remaining 37.6% of the Variable (Y) not covered in the study. This showed that the Spiritual Intelligence Variable (X1) has a significant impact on the Performance Variable (Y).